The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1159/000049707
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Liver and Lung Injury after Hepatic Ischemia and Reperfusion by a Cytokine-Suppressive Agent, FR167653

Abstract: Background: Hepatic ischemia/reperfusion (I/R) injury is an important clinical problem and leads to the release of the proinflammatory cytokines, TNF-α and IL-1. These cytokines play important roles in the induction of polymorphonuclear neutrophil (PMN) activation and infiltration, and induce not only localized hepatic injury but also remote organ injury, especially pulmonary injury. Using a total hepatic ischemia model in rats, we tested our hypothesis that suppression of TNF-α and IL-1 by FR167653 ameliorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
2
17
0
1
Order By: Relevance
“…These cytokines play important roles in the induction of polymorphonuclear neutrophil (PMN) activation and infiltration, and induce not only localized hepatic injury but also remote organ injury. In the study of Hato et al [46] , neutrophil accumulation and the content of cytokines, including TNF-␣ , and IL-1 ␤ , were increased in the reperfused liver. Similarly, Tsuchihashi et al [47] , who studied the role of cytokines in I/R injury of the liver tissue, suggested that I/R led to the expression of TNF-, IL-1 ␤ , IL-6, in the reperfused rat liver model, and the expressed cytokines are expected to aggravate I/R injury.…”
Section: Discussionmentioning
confidence: 91%
“…These cytokines play important roles in the induction of polymorphonuclear neutrophil (PMN) activation and infiltration, and induce not only localized hepatic injury but also remote organ injury. In the study of Hato et al [46] , neutrophil accumulation and the content of cytokines, including TNF-␣ , and IL-1 ␤ , were increased in the reperfused liver. Similarly, Tsuchihashi et al [47] , who studied the role of cytokines in I/R injury of the liver tissue, suggested that I/R led to the expression of TNF-, IL-1 ␤ , IL-6, in the reperfused rat liver model, and the expressed cytokines are expected to aggravate I/R injury.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it seems reasonable to propose that hepatic ischemia/ reperfusion (I/R) injury leads to the release of the cytokines. In the study of Hato et al (2001) neutrophil accumulation and the content of cytokines, including TNF-α and IL-1β, were increased in the reperfused liver. Similarly, Tsuchihashi et al (2006) who studied the role of cytokines in I/R injury of the liver tissue, suggested that I/R led to the expression of TNF-α, IL-1β, IL-6 in the reperfused rat liver model, and the expressed cytokines are expected to aggravate I/R injury.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, transient interruption of hepatic inflow is sometimes necessary during partial hepatectomy (10,14). The lung is one of the most susceptible organs to systemic inflammation-related injury, secondary to liver ischemiareperfusion (7,16,36), intestinal ischemia-reperfusion (6, 37), and renal ischemia-reperfusion (11,17).…”
mentioning
confidence: 99%